The implementation of project work by selected grade 10 life science teachers in Namibia - Angula, Alina Hambelela (Rhodes University, Faculty of Education, Department of Education, 2009)
Prior to independence in Namibia in 1990 the education system of the day did not encourage the majority of Namibian learners to explore and investigate the wonder of the natural and physical world. The post independence education system has nurtured the study of the sciences and has emphasized participation, problem solving and independent studies. The inclusion of projects and other independent studies has been regarded as a key vehicle to develop scientific understanding and competencies related to this understanding. However, very few studies have hitherto investigated the teachers' understanding and implementation of projects in the Namibian context. This study investigates how Grade 10 Life Science teachers understand and implement projects in selected schools in Namibia. The study focused on two teachers in two schools, a combined and a senior secondary school in the Oshikoto educational region of Namibia. The research was conducted through an interpretive case study aiming to gain a better understanding about the implementation of projects in schools. Data were collected through semi-structured interviews, classroom observation and document analysis. The findings indicate that despite the focus on projects in the Life Science syllabus and broad curriculum, policy documents do not give detailed guidelines on how projects should be planned, organized and assessed. The results revealed that knowledge about projects and their implementation is primarily informed by practical activities rather than the critical enquiries or investigations required by the Life Science curriculum policy. The study also revealed that despite the in-service training received by the two teachers participating in this study on syllabus interpretation, it is apparent from the findings that project work in these in-service programmes was neglected. This has further hampered teachers' understanding and implementation of projects. The findings of this study point to a need for project guidelines as well as in-service programmes in this area if the stated nature and role of projects in the context of Namibian education policy is to be achieved.
Keywords: Education -- Namibia; Life sciences -- Study and teaching (Secondary) -- Namibia; Project method in teaching -- Namibia; School improvement programs -- Namibia; Teachers -- Training of -- Namibia; Curriculum planning -- Namibia; Educational change -- Namibia